IMPACT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) IN INDONESIA: A CASE STUDY OF GENERAL MINING INDUSTRIES - Ukar Wijaya Soelistijo (Indonesian Mining Journal, 2013)
Mining companies as the stakeholder of the community should implement community development (CD) as a translation of corporate social responsibility (CSR). In other words, they should involve business activities for developing humankind. The application of CSR in the general mining in Indonesia is expected to encourage min- ing company to allocate its profit for developing the local people who live around mining area. The quantitative models for evaluating the CD impact include net social gains (NSG) and net gain coefficient (NGC). The NGC shows that the value between 1 to 23% of the companies’ revenue has satisfied the local people. The values could be increased in the future to make beneficial for the regional sustainable development.